THE IMPLEMENTATION OF JAZZ CHANTS TO ENHANCE VOCABULARY MASTERY AMONG EFL YOUNG LEARNERS - Yanti, Novi; Suryani, Suryani; Susiani, Rini (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
This study aims to improve students’ vocabulary mastery in English learning using the Jazz Chants technique. This study uses pre-experimental research with quantitative methods. There were 35 students from fifth grade of MIN 09 Banda Aceh who were involved as respondents in this study. This study used pre-test and post-test research instrument. The test consisted of 10 questions in which the students had to recognize the vocabulary about body parts. The data then was analyzed using SPSS 22 version. The findings show that the use of Jazz Chants technique is significantly improving students’ understanding of vocabulary mastery. This is because students learn and practice to recognize the body parts vocabulary using Jazz Chants technique. It is evidenced by the average pretest score of writing vocabulary before treatment, namely 55.14, while the average score after being given treatment are 92.29. The paired T test shows that the t value obtained is -37.142 with a p value of 0.000. This means that there is significant increase in students’ vocabulary mastery after using the Jazz Chants technique. Thus, it is recommended for English teachers to use Jazz Chants technique in teaching vocabulary to students